The Impact of Flipped Classroom Model on Student’s Learning : Study Meta-analysis - Fryan Sopacua; Loso Judijanto; Ellina Rienovita; Sukini Sukini; Nenni Triana Sinaga; Mohammad Edy Nurtamam; Novianty Djafri; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2024)
The flipped classroom model has become a popular learning model in recent years. This model reverses the traditional concept of learning by moving key learning activities outside the classroom, allowing students to learn independently through videos, modules, or other learning resources. This study aims to analyze the impact of the flipped classroom model on student learning through meta-analysis. The meta-analysis was conducted by collecting and analyzing the results of 14 primary studies examining the effectiveness of the flipped classroom model compared to traditional learning methods. Data analysis is a quantitative analysis with a JSAP application. The results of this study concluded that the meta-analysis results showed that the flipped classroom model had a significant positive impact on student learning with an overall effect size of 0.826; P < 0.001 is included in the high effect size category. The findings show that students who participate in learning with the flipped classroom model have better learning outcomes compared to students who follow traditional learning.